Towards a Geography of Nepalese Cuisine - Seddon, David (The Third Pole: Journal of Geography Education, 2014)
This is the first part of an article which proposes to break new ground in developing a conceptual framework for and presenting a preliminary empirical analysis of ‘the geography of Nepalese cuisine’. This part of the article sets outsome of the elements required for an exploration of national, regional and local cuisines. It elaborates the concept of ‘cuisine’ as a historical but constantly evolving socio-economic and cultural construct (a food tradition) within a more-or-less defined geographical area. It considers the significance of ‘food availability’ and the ways in which the ‘natural’ world is classified and categorized to define what is considered edible and what is not. It explains how food preparation and processing transforms an animal, fish or plant into a food stuff or ingredient and examines how food preparation, production (including cooking) and presentation may differ and may be associated with different styles of cuisine (high and low, complex and simple, etc.). It introduces a distinction between national, regional and local cuisines and briefly considers the treatment of ‘Indian’ cuisine. DOI: http://dx.doi.org/10.3126/ttp.v8i0.11518 The Third Pole: Journal of Geography Vol.8-10, pp. 62-72: 2010